The Unusual Suspects: Multiple-Perpetrator and Multiple Concurrent Victim Sexual Homicide - Higgs, Tamsin (International journal of offender therapy and comparative criminology, 2019)
Sexual homicide typically implies a crime involving two people: perpetrator and victim. Thus, multiple-perpetrator and multiple concurrent victim sexual murderers are unusual, empirically invisible due to their exclusion from (or burying within) research samples. The present study examines 21 such cases of male sexual murderers having perpetrated at least one sexual homicide either together with a co-offender or alone but killing two victims at once. The aim was to investigate just how unusual, or not, these cases may be in relation to current scientific understanding of sexual murderers and their crimes. A descriptive analysis of offenses (co-offender and offender-victim dynamics, modus operandi) and offender characteristics is presented. Main findings, that multiple-perpetrator and multiple concurrent victim sexual murderers are not so unusual in that they are well conceptualized through application of the established sexualized, grievance, and rape murderer typology, are discussed in relation to clinical and empirical implications.